Leadership in Biblical Teachings in a Multicultural Society Through Christian Religious Education (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted to examine global developments in an increasingly complex and dynamic multicultural society, so that Christian Religious Education (PAK) is important to adapt to the challenges and developments that exist. Things that are currently present in society are plurality, multiculturalism, ethical challenges, technological developments, social change, conflicts between communities, and consumerism. Based on these emerging issues, the importance of integrating PAK values into character development in forming leaders that are relevant to the global context is highlighted. In terms of leadership in biblical teachings, Christian leaders must uphold the rules contained in the teachings of Christianity and be able to keep up with global developments in a multicultural society. This becomes a challenge for a leader who upholds the teachings of the Bible to be able to respect the diversity of views and opinions to be able to produce decisions that are universal for the whole community. The research method in this paper uses descriptive qualitative with a systematic literature review and is supported by the literacy of international journals, theological articles, and theological teaching books. Based on the results of the research study that has been carried out, leadership in the teachings of the Bible in a society that has diversity, there are teaching values contained in the PAK that can generally be applied to all people without discrimination because these values are in accordance with universal values. The conclusion that can be drawn in this study is that leaders have an important role in building unity in a diverse society by appreciating diversity and being able to overcome conflict, namely by practicing the principles of Christian leadership values to form good and effective leaders.